2011
DOI: 10.1073/pnas.1014769108
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin up-regulation of pyruvate kinase isoenzyme type M2 is critical for aerobic glycolysis and tumor growth

Abstract: Although aerobic glycolysis (the Warburg effect) is a hallmark of cancer, key questions, including when, how, and why cancer cells become highly glycolytic, remain less clear. For a largely unknown regulatory mechanism, a rate-limiting glycolytic enzyme pyruvate kinase M2 (PKM2) isoform is exclusively expressed in embryonic, proliferating, and tumor cells, and plays an essential role in tumor metabolism and growth. Because the receptor tyrosine kinase/PI3K/ AKT/mammalian target of rapamycin (RTK/PI3K/AKT/mTOR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
441
5
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 503 publications
(471 citation statements)
references
References 53 publications
13
441
5
3
Order By: Relevance
“…MEFs was subjected to microarray on an Affymetrix GeneChip system with the Affymetrix Mouse Genome 430 2.0 Array, and data were analyzed using the Partek Express software (31).…”
Section: Methodsmentioning
confidence: 99%
“…MEFs was subjected to microarray on an Affymetrix GeneChip system with the Affymetrix Mouse Genome 430 2.0 Array, and data were analyzed using the Partek Express software (31).…”
Section: Methodsmentioning
confidence: 99%
“…However, an earlier report has indicated that peroxide treatment of cells does result in nuclear localization of PKM2 [5]. This finding also raises the question as to whether the several different post-translational modifications of PKM2 that have been reported, including tyrosyl phosphorylation [1,8], prolyl hydroxylation [9,13], acetylation [14], mono ubiquitination [15], sumoylation [2] and cysteine oxidation [12], are integrated to regulate PKM2's activation of transcriptional programmes [9,10,16] in response to cell signaling events.…”
mentioning
confidence: 44%
“…This protein causes an increase in glycolysis and the metabolism of glycine, serine, and pyrimidine, promoting stem cell proliferation in several types of cancers. In addition, IDH1 mutants and HMGCR have potential oncogenic activities [51,52]. The mTOR up-regulation of PKM2 through HIF1A-mediated transcriptional activation is important for aerobic glycolysis and tumor growth [53].…”
Section: Abnormal Cancer Metabolism and Tumor Microenvironmentmentioning
confidence: 99%
“…Furthermore, tumor cells produce large quantities of secreted lactate, which causes an acidic environment to stimulate reprogramming gene expression and the genesis of TME [8,[45][46][47][48][49][50][51][52][53][54][55][56][57]. Key genes responsible for abnormal cancer metabolism, such as DGLC and several other aerobic metabolic enzymes, can be targeted using their pharmacological inhibitors in glucose, glutamine, and fatty acid metabolic pathways.…”
Section: Correction Of Abnormal Cancer Metabolismmentioning
confidence: 99%